Phenolic Compounds Natural Sources, Importance and Applications - Soto-Hernandez, Marcos; Palma-Tenango, Mariana; del Rosario Garcia-Mateos, Maria (IntechOpen, 2017)
Phenolic compounds as a large class of metabolites found in plants have attracted attention since long time ago due to their properties and the hope that they will show beneficial health effects when taken as dietary supplements. This book presents the state of the art of some of the natural sources of phenolic compounds, for example, medicinal plants, grapes or blue maize, as well as the modern methods of extraction, quantification, and identification, and there is a special section discussing the treatment, removal, and degradation of phenols, an important issue in those phenols derived from the pharmaceutical or petrochemical industries.